Characterization of Serogroup A Neisseria meningitidis from Invasive Meningococcal Disease Cases in Canada Between 1979 and 2006: Epidemiological Links to Returning Travellers - Angela M Sloan; Averil M Henderson; Raymond SW Tsang (Canadian Journal of Infectious Diseases and Medical Microbiology)
INTRODUCTION: Serogroup A Neisseria meningitidis has repeatedly caused epidemics of invasive meningococcal disease (IMD) in developing nations since the 1960s. The present study is the first detailed study of serogroup A bacteria isolated in Canada.